Fortifikasi Pakan Ikan Berbasis Limbah Pertanian Untuk Meningkatkan Pertumbuhan Dan Hasil Lele Sangkuriang (Clarias gariepinus): Fortifikasi Pakan Ikan Berbasis Limbah Pertanian Untuk Meningkatkan Pertumbuhan Dan Hasil Lele Sangkuriang (Clarias gariepinus) - Hamron, Novita; Kesuma, Bambang Wijaya; Oktamalia; Sari, Dia Novita; Togatorop, Eny Rolenti (UNIB Press, 2025)
The development of fish feed fortification technology based on agricultural waste is one of the potential solutions to reduce feed production costs. Fish feed fortification can be derived from animal and plant sources, provided that the fortification ingredients contain protein, carbohydrates, fat, and other nutrients. Rice bran, an agricultural by-product, contains carbohydrates that can be utilized as raw material in fish feed formulation. The objective of this study was to analyze the effect of fortified fish feed made from silk worm meal and fish meal fortified with rice bran waste on the growth and yield of Sangkuriang catfish (Clarias gariepinus). The research method employed a Completely Randomized Block Design (CRBD) with four treatments, namely: A (2.25% tapioca flour + 0.75% rice bran flour), B (2% tapioca flour + 1% rice bran flour), C (1.5% tapioca flour + 1.5% rice bran flour), and D (0.75% tapioca flour + 2.25% rice bran flour). Each treatment was replicated three times, resulting in a total of 12 experimental units. The results showed that treatment D (0.75% tapioca flour + 2.25% rice bran flour) was the best artificial feed formulation for Sangkuriang catfish grow-out, as indicated by higher absolute length gain, absolute weight gain, survival rate, and feed conversion ratio. The nutritional content of treatment D feed formulation (1:3), consisting of 0.75% tapioca flour + 2.25% rice bran flour, was 1.85% carbohydrate, 12.79% fat, and 31.01% protein.